Pangenomic analysis of Wolbachia provides insight into the evolution of host adaptation and cytoplasmic incompatibility factor genes - Liu, Bo; Ren, Ye-Song; Su, Cheng-Yuan; Abe, Yoshihisa; Zhu, Dao-Hong (Frontiers in Microbiology, 2023)
The genus Wolbachia provides a typical example of intracellular bacteria that infect the germline of numerous invertebrate species worldwide. Despite their importance as biological regulators of invertebrates, their evolution, divergence and host adaptation of these bacteria have been poorly studied at the whole-genome level. Here, we used publicly available Wolbachia genomes to reconstruct their evolutionary history and explore their adaptation under host selection. Our findings indicate that segmental and single-gene duplications in single monophyletic Wolbachia lineages (including supergroups A and B) may be responsible for improving the ability to adapt to a broad host range in arthropod-infecting strains. In contrast to A strains, high genetic diversity and rapidly evolving gene families occur in B strains, which may promote the ability of Wolbachia B strains to adapt to new hosts and their pandemic spreading. In addition, we hypothesize that there might have been two independent horizontal transfer events of cif genes in two sublineages of supergroup A strains. Interestingly, during the independent evolution of supergroup A and B strains, the rapid evolution of cif genes in Wolbachia B strains resulted in the loss of their functional domain, reflected in a possible decrease in the proportion of induced cytoplasmic incompatibility (CI) strains.